Misplaced Cu-T as a Cause of Recurrent Urinary Tract Infection - A Rare Case - Rijvi, Shiffin; Shaikh, Azfar Uddin; Rima, Shamim; Marat, Khairun Nesa; Haideru, Tasnim; Hasanv, Noor Md Enamul; Jishaw, Nafiza Islam (Bangladesh Journal of Obstetrics & Gynaecology, 2025)
Abstract not available Bangladesh J Obstet Gynaecol, 2023; Vol. 38(2): 107-110